Effect of irrigants on the color stability, solubility, and surface characteristics of calcium-silicate based cements - Selen Küçükkaya Eren; Sevinc Askerbeyli Örs; Hacer Aksel; Şenay Canay; Duygu Karasan (Restorative Dentistry & Endodontics, 2022)
ObjectivesThis study aimed to investigate the color stability, solubility, and surface characteristics of 3 calcium silicate-based cements (CSCs) after immersion in different solutions.Materials and MethodsProRoot white mineral trioxide aggregate (MTA), Biodentine, and Endosequence Root Repair Material (ERRM) were placed in cylindrical molds and stored at 37°C for 24 hours. Each specimen was immersed in distilled water, 5% sodium hypochlorite (NaOCl), 2% chlorhexidine, or 0.1% octenidine hydrochloride (OCT) for 24 hours. Color changes were measured with a spectrophotometer. Solubility was determined using an analytical balance with 10−5 g accuracy. The surface characteristics were analyzed using scanning electron microscopy and energy-dispersive spectroscopy. Data were analyzed using 2-way analysis of variance, the Tukey test, and the paired t-test.ResultsMTA exhibited significant discoloration in contact with NaOCl (p < 0.05). White precipitation occurred on the surfaces of Biodentine and ERRM after contact with the solutions, and none of the materials presented dark brown discoloration. All materials showed significant solubility after immersion in the solutions (p < 0.05), irrespective of the solution type (p > 0.05). The surface topography and elemental composition of the samples showed different patterns of crystal formation and precipitation depending on the solution type.ConclusionsAll materials presented some amount of solubility and showed crystal precipitation after contact with the solutions. Biodentine and ERRM are suitable alternatives to ProRoot MTA as they do not exhibit discoloration. The use of OCT can be considered safe for CSCs.